P412 Effectiveness of ustekinumab in fistulising perianal Crohn′s disease refractory or intolerant to anti-TNF. (27th May 2021) - Carpio, D; Calviño-Suarez, C; Martínez-Cadilla, J; Molina, G; Vázquez-Rey, M T; Martí, E; Fernández-Salgado, E; Barreiro-de Acosta, M; Hernández, V; Echarri, A; Diz-Lois, M T; Baz, A
Abstract: Background: The management of fistulising perianal Crohn′s disease (pCD) is a challenging problem for patients and physicians. New therapeutic alternatives are needed, particularly in anti-TNF refractory patients. Data regarding ustekinumab (UST) effectiveness in pCD are scarce. Our aim was to evaluate the clinical and radiologic effectiveness of UST in pCD patients refractory or intolerant to anti-TNF. Methods: We conducted a multi-center retrospective observational study. All patients with anti-TNF refractory pCD treated with UST were evaluated. Demographic and clinical variables including concomitant drugs were registered. Clinical response was evaluated at 16 weeks and 12 months and was defined as a reduction of 50% of draining fistulas or a marked reduction in fistula drainage. In patients with a magnetic resonance imaging (MRI) before and after treatment initiation, radiologic response was defined according to Ng Score (healed, partial response, unchanged, deterioration). Results: Thirty-two patients were included, 68.8% female, median age 44, 11 (IQR 36.28-48.56). Median time from diagnosis to UST initiation was 12.94 years (IQR 7.52-19.52), 90.6% had received previously 2 anti-TNF (37.5% also vedolizumab) and 46.9% had more than 2 fistulas. In 22 patients (68.8%) pCD was the main indication for UST treatment while in the remaining 31.2% the main indication was luminal disease. Fifteen patients (46.9%) received antibiotics at the initiation of UST, 8 (25%) combo therapy with thiopurines and 21 (65.6%) had setons. Patients received a 6mg/kg IV dose and 87.5% received 90mg/8 week SQ for maintenance. Dose intensification was needed in 20 patients (62.5%) at a median of 13 months (IQR 8.00-19.5). Fifteen patients (46, 9%) achieved clinical response at week 16, while 18/30 (60%) had clinical response at 12 months (three of them were in clinical remission). Nineteen patients (59, 4%) had an MRI performed pre and post-treatment at a median of 15 months (IQR 10-19). 10/19 patients (52.6%) achieved a radiological response although no patient had all fistulas healed. In the multivariate analysis the only factor associated with clinical response at 12 months was the presence of setons at UST initiation (OR 7.0; IC95% 1.3-37.9). There were no factors significantly associated with radiological response or clinical response at week 16. Four patients experienced adverse effects (three perianal abscesses and one transient skin rash). Conclusion: Ustekinumab was effective in achieving clinical and radiological response in anti-TNF-refractory fistulising pCD patients, although clinical and radiological remission was rare. Most patients needed UST dose intensification in this highly refractory cohort. Adverse effects were infrequent, mainly perianal abscesses.